Periodicidade do crescimento de espécies arbóreas da Floresta Estacional Semidecidual no Sul do Brasil - Blagitz, Marcela [UNESP]; Botosso, Paulo Cesar; Bianchini, Edmilson; Medri, Moacyr Eurípedes (Instituto de Pesquisa e Estudos Florestais (IPEF), 2016)
Although seasonality is less evident in the tropics than in temperate ones, many tropical species present rhythmic growth. The stem circumference growth (SCG) evaluation will provide information on the development of tree species in this region. This study aimed to evaluate the SCG of 11 tree species of a tropical semi-deciduous forest in Southern Brazil. Two hypotheses were advanced: (i) seasonality of the trees SCG exist and it is related to climatic variations of the study area; (ii) individual characteristics (tree height, degree of occupancy by lianas, sociological position, deciduousness and diameter at breast height) influence the circumference cumulative growth. To detect the SCG periodicity, permanent dendrometric bands were fixed around the stem (diameter at breast height, or DBH) of 156 individuals. Growth was monitored monthly for a period of 18 months. Correlations of monthly SCG with precipitation, temperature and photoperiod were made to verify the environmental parameters' influence and a covariance analysis was performed to enquire if individual characteristics also affected cumulative increase in circumference. The species showed a seasonal pattern of SCG with higher growth rates from October to December and environmental parameters operate jointly - especially photoperiod and the temperature - To promote growth seasonality, confirming the first hypothesis. Considering the individuals characteristics, only the trunk diameter was negatively correlated with increasing cumulative circumference (b= -0.32; p=0.02), partially accepting the second hypothesis.
Growth periodicity of trees species from a seasonal semi-deciduous forest in Southern Brazil
Keywords: Atlantic rain forest; Deciduousness; Seasonality; Successional groups; Tropical forest